An experimental method for measuring VOC emissions from individual human whole-body skin under controlled conditions. (15th August 2020) - Zou, Ziwei; He, Junzhou; Yang, Xudong
Abstract: The human body is an important source of volatile organic compounds (VOCs), especially in densely occupied environments. This research provides an experimental method for separately measuring the whole-body skin emissions of an individual person under controlled conditions. The designed experimental device consisted of a 1.5 m 3 stainless steel test chamber and a transition chamber surrounding it. The environmental parameters such as temperature and background concentrations were controlled in both the test chamber and the transition chamber. During measurement, a human subject with standard clothing sat calmly in the test chamber operating in an airtight mode, and breathed through the respiratory channel with a mask tightly covering the face. A male subject was tested to verify the feasibility and repeatability of this experimental method. The results showed that VOCs emitted from the whole-body skin had accumulated in the test chamber air and changed linearly, indicating that the whole-body skin was a nearly stable source of VOCs during the experimental period. The 37 VOCs emitted from this subject's skin showed clear qualitative results, including alcohols, aldehydes, ketones, alkanes, aromatics, esters, alkenes, and acids, and the first three kinds contributed the most to the emissions. The reported VOC emission rates ranged from 0.8 to 86.3 μg/h, and were highly consistent in magnitude with those of the same compounds in the literature. The high repeatability of this experimental method suggested its applicability to explore human skin emissions of more subjects and under various conditions in the future. Highlights: An experimental method was proposed to measure VOC emissions from whole-body skin of a single person. The method can effectively separate the skin and breath emissions. High detectability and repeatability of the method showed good potential for studying human emissions.